Therapeutic Exercise for Musculoskeletal Injuries - Houglum, Peggy A.; Series editor: Perrin, David H. (Champaign Human Kinetics, 2010)
Therapeutic Exercise for Musculoskeletal Injuries, Third Edition, contains an extensive explanation of the science and application involved in developing safe therapeutic programs for the general population as well as individualized programs for specific audiences.
Include Illustrations, Glossary, References and Index.
Keywords: Sports injuries--Exercise therapy -- Musculoskeletal system--Wounds and injuries -- Sports injuries--Treatment